First-year all-cause kidney allograft loss: descriptive clinical trajectories of 92 events from a 17-year German transplant center cohort - Ulrich Jehn; Arina Lokschin; Felix Becker; Philipp Houben; Hermann Pavenstädt; Stefan Reuter (BMC Nephrology, 2026)
Abstract Background First-year kidney allograft loss comprises death with a functioning graft (DWFG) and death-censored graft loss (DCGF), each arising from diverse clinical causes. Few studies have examined how endpoint-specific causes are distributed over the first post-transplant year within the same cohort. Methods We retrospectively reviewed adult kidney transplant events performed at a German transplant center between 2007 and 2023. For each first-year all-cause graft-loss event, endpoint type and one primary cause were assigned from the documented clinical sequence; additional complications were retained as contributing events. Granular source causes were mapped into higher-order groups defined before examination of their distribution across 0–30, 31–90, and 91–365 day windows. Results Among 1400 adult kidney transplant events, 92 first-year all-cause graft-loss events occurred (6.6%, 95% CI 5.4-8.0): 57 DCGF and 35 DWFG. The leading DCGF cause group was vascular/thrombotic or microangiopathic loss (18/57), followed by infection/sepsis (8/57), rejection (7/57), and cardiorenal decompensation/cardiac failure (6/57). Among DWFG events, cardiovascular causes (15/35) and sepsis (9/35) predominated. The proportion of events classified as DWFG increased from 5/32 in the first 30 days to 7/15 at days 31–90 and 23/45 at days 91–365. Six DCGF events were followed by recipient death within the same first year. Conclusions First-year all-cause graft loss contained distinct cause and timing patterns. Early losses were predominantly vascular or perioperative DCGF, whereas later events increasingly reflected cardiovascular, infectious, and other medical causes, including DWFG. These findings support phase-specific surveillance and prospective multicenter validation using prespecified assessment of primary and contributing causes.